Progress on additive manufacturing of 600 ℃ high-temperature titanium alloys - MI Guangbao; TAN Yong; CHEN Hang; LI Peijie; ZHANG Xuejun (Journal of Aeronautical Materials, 2024)
Key components used in the high-pressure compressor of advanced aero engines operating in the 550-600 ℃ range have an urgent demand for 600 ℃ high-temperature titanium alloy. However，the use of casting，forging，and other traditional processing techniques is not sufficient to meet the requirements for gradient or composite structures，functional integration components and complex components that are difficult to form. Additive manufacturing is an advanced manufacturing technology that offers unique advantages such as material design-manufacturing integration and complex design-customization integration. It provides a new approach to the development of new materials and technologies of 600 ℃ high-temperature titanium alloy. Currently，attention is being paid to the processing of 600 ℃ high-temperature titanium alloy by using additive manufacturing techniques at home and abroad，focusing on the relationship among materials，processing，structures，and properties. Firstly，this paper reviews the research on 600 ℃ high-temperature titanium alloy in brief，introduces the microstructure characteristics of deposited and post-treated states of 600 ℃ high-temperature titanium alloy under different additive manufacturing processes，and analyzes key properties such as tensile properties，creep properties，thermal fatigue properties，and antioxidant properties. Then，the research progress of composite materials based on 600 ℃ high-temperature titanium alloy and gradient structure built by additive manufacturing is discussed. Finally，the prospects are provided for research directions including the development of 600 ℃ high-temperature titanium alloy materials for additive manufacturing，exploration of hybrid manufacturing processes，defect control，and establishment of performance evaluation standards.